Sobre nubes y relojes: aproximación al problema de la racionalidad y libertad del hombre (2013)
ABSTRACT: This review discusses the text “On clouds and Clocks” by Karl Popper, in which the author presents his views on the issue of determinism and indeterminism. First, a discussion on determinism and indeterminism is presented from three analysis categories: ontological, methodological and ethical. Then, Popper's evolutionist approach regarding the issue of determinism is analyzed. Finally, some of the epistemological and ethical consequences of determinism on the field of health are presented.